Growth Elasticities of Poverty Reduction - Ravallion, Martin (Journal of Income Distribution®, 2022)
Thirty years ago, Nanak Kakwani provided elegant nonparametric formulae for the point elasticities of poverty measures with respect to changes in the mean of the distribution, thus analytically linking those measures to key macroeconomic aggregates. Numerous insights are found in Kakwani’s elasticities. Rising inequality, measurement errors, discrepancies between surveys and national accounts, and changing ideas about what ‘poverty’ means are all reasons why the impacts of growth on poverty observed in practice can be substantially lower than suggested by Kakwani’s elasticities. These elasticities should not be treated as structural parameters. Rather, they can vary over time and place in systematic ways.